INTEGRATED COKE PLANT AUTOMATION AND OPTIMIZATION USING ADVANCED CONTROL AND OPTIMIZATION TECHNIQUES - MUHLBAIER, MIKE; EVATT, SHARLA; KAPLAREVIC, MILOS; KESAVAN, PARTHASARATHY; RUSSELL, KATIE; KHANNA, RAKSHAK; CHUN, PETER; QUANCI, JOHN FRANCIS; ZIEGLER, JACK (2022)
The present technology is generally directed to integrated control of coke ovens in a coke plant in order to optimize coking rate, product recovery, byproducts and/or unit lime consumption Optimization objectives are achieved through controlling certain variables (called control variables) by manipulating available handles (called manipulated variables) subject to constraints and system disturbances that affect the controlled variables.